Access to health services in Brazil by transsexuals women: an integrative review (Research, Society and Development, 2021)
The objective is to analyse the Brazilian scientific production about the access to health services by transsexual women in primary care of the SUS. This integrative review was conducted from January 2020 to January 2021, in the database Medical Literature Analysis and Retrieval System Online, Scientific Electronic Library Online, Literatura Latino-Americana e do Caribe em Ciências da Saúde, Cumulative Index to Nursing and Allied Health Literature and Banco de Dados em Enfermagem, for the period from 2013 to 2020 and selected from the guide question: How does access to health services be given in primary care of the SUS by women transsexuals? The review was composed by eleven articles. The publications found barriers in the implementation of politics for trans population, as the social name disrespect in the health unities. Moreover, the concentration of most studies in the Southest makes harder to make an overview of access in Brazil. The scientific production analysed showed the problems in the access and the need to educate SUS primary care health professionals about the needs of trans women.